Dual Cross-Linking Systems of Functionally Photo-Cross-Linkable and Thermoresponsive Polyphosphazene Hydrogels for Biomedical Applications - Potta, Thrimoorthy; Chun, ChangJu; Song, Soo-Chang (AMER CHEMICAL SOC, 2010)
Photo-cross-linkable, functionalized, and thermosensitive polyphosphazenes were synthesized to develop a dual cross-linking system with properties of mechanically suitable strength and controllable biodegradation for injectable biomedical applications. The aqueous solutions of the polymers exhibited sol gel transition behaviors against temperature. The incorporated methacrylate groups were photo-cross-linked upon UV light under mild conditions, which resulted in the formation of compact three-dimensional networks. The thermoresponsive hydrophobic interactions at body temperature facilitated the rapid dual cross-linking accomplishment of the photo-cross-linking even under mild conditions. The characteristics of the polymers such as pore size and density showed that the inner three-dimensional networks depended on the degree of cross-linking of methacrylate units. Mechanical properties of the eel were also improved several folds after developing the photo-cross-linking in the network from the in vivo degradation studies. The results demonstrate that the photo-cross-linkable and thermoresponsive polyphosphazenes have great potential as injectable, biodegradable, and controllable carriers for various biomedical applications by tuning the mechanical gel property and the degradation rate.
Keywords: DRUG-DELIVERY; CYTOCOMPATIBILITY; POLYMERIZATION; DEGRADATION; SCAFFOLDS; NETWORKS; RELEASE; CELLS; GEL